2016
DOI: 10.1021/acs.biochem.6b00231
|View full text |Cite
|
Sign up to set email alerts
|

Thioflavin T-Silent Denaturation Intermediates Support the Main-Chain-Dominated Architecture of Amyloid Fibrils

Abstract: Ultrasonication is considered one of the most effective agitations for inducing the spontaneous formation of amyloid fibrils. When we induced the ultrasonication-dependent fibrillation of β2-microglobulin and insulin monitored by amyloid-specific thioflavin T (ThT) fluorescence, both proteins showed a significant decrease in ThT fluorescence after the burst-phase increase. The decrease in ThT fluorescence was accelerated when the ultrasonic power was stronger, suggesting that this decrease was caused by the pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
13
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 60 publications
(186 reference statements)
1
13
0
Order By: Relevance
“…It appears, then, that the DLPC-induced changes in ThT fluorescence and morphological differences observed by TEM are the result of more surface level disruptions. It has previously been shown that A␤ fibrils can adopt a pseudotransition state, termed the molten globule state, in which side chain packing at the fiber surface becomes perturbed (22). The molten globule state was defined by a reduction in ThT fluorescence and truncation of the fibrillar structure while the ␤-strand signal was maintained in CD spectroscopy, similar to what we have observed in the presence of DLPC (28).…”
Section: Resultssupporting
confidence: 81%
See 4 more Smart Citations
“…It appears, then, that the DLPC-induced changes in ThT fluorescence and morphological differences observed by TEM are the result of more surface level disruptions. It has previously been shown that A␤ fibrils can adopt a pseudotransition state, termed the molten globule state, in which side chain packing at the fiber surface becomes perturbed (22). The molten globule state was defined by a reduction in ThT fluorescence and truncation of the fibrillar structure while the ␤-strand signal was maintained in CD spectroscopy, similar to what we have observed in the presence of DLPC (28).…”
Section: Resultssupporting
confidence: 81%
“…It is likely that DLPC is sufficiently mild in its perturbations so as to not fully denature and instead stabilize this unfolding transition state. Although we observed that DLPC inhibits A␤ aggregation through a combination of detergent-like interactions and stabilization of membrane-associated globulomers, it is likely that the fibrils are primarily altered through interactions with the surface of DLPC LUVs, which promote disorder in the traditionally ordered side chain packing of the fibril (22,60). This increased disorder can facilitate a reduction in ThT binding and fluorescence.…”
Section: Resultsmentioning
confidence: 74%
See 3 more Smart Citations